External electric effect on the adsorption of benzene on Mg4O4 cluster: A DFT investigation - Maryam Taheri Jam; Reza Ghiasi; Sahar Baniyaghoob (Results in Chemistry, 2025)
In this work, the adsorption of benzene on the Mg4O4 cluster was illustrated in the absence and presence of external electric field (EEF) along x-axis by LC-ωPBE model. EEF effect on the adsorption energy values was investigated. Variations in the dipole moment, polarizability as well as structural factors were exhibited in the presence and absence of EEF. Dependencies of EEF strength on theses parameters were explored. Linear correlations between adsorption energy, dipole moment and polarizability values with EEF strength were provided.